Knowledge and Participation: Wich Democracy? - Saiani, Paolo Parra (Universidad Nacional de La Plata. Facultad de Humanidades y Ciencias de la Educación, 2010)
A new impetus for recollecting information seems regaining appeal, maybe heir of the "social indicators movement". The movement was an heir to the supporters of quantification in the Social Sciences, as numbers were believed to be objective and scientific per se and information was considered to be a citizen's right. The study of society in its various dimensions has stimulated the search for and construction of statistical indicators and indices. The search for a better way of studying the progress of societies has often led to inappropriate uses of indicators and measures. GNP, for example, has been commonly considered to be an indicator of well-being. The lack of a conceptual frame for studying well-being is not the only problem, nor even the greatest. Of similar importance - or even greater - are the meager statistical skills of journalists, policy-makers and - in general - the public. All together, these elements facilitate limiting the use of data in public debate. In this paper, I will consider the shift from political arithmetick to modern social reports [par. 1]; the success of quantification in the administration of the State [par. 2]; the misuses of quantification [par. 3]; the current non-use of quantification and the search for contextual conditions that interfere with the transformation of information into knowledge [par. 4]